Supporting Factors of Development School Library Based on Information Technology - Rahmah, Elva; Emidar, Emidar; Zulfikarni, Zulfikarni (D3 Teknisi Perpustakaan Fakultas Vokasi Universitas Airlangga, 2018)
The existence of a school library is a must. Based on the National Education Standards, eachschool is required to have a library. In its management, the library must be managed byappropriate management personnel and competent in their fields. In line with thedevelopment of science and technology that continues to develop school libraries need to bemanaged and utilized for the benefit of education through an appropriate forum, namely theschool library. Descriptive research method with a qualitative approach. Collecting datathrough observation, interviews and document analysis. Subjects in this study were schoolprincipals, library heads, library staff, visitors, events, facts, documents and various forms ofefforts, school library programs or activities. The object in this study is the development of aschool library based on information technology carried out in SMAN 2 and SMA 3 KotaPadang. The results showed that the factors influencing the development of informationÂ technology-based school libraries in State High School 2 and State 3 High School in PadangCity could be identified into four, namely human resources, information resources, funding,and infrastructure in the school library.Â